Traumatic Stress Produces Delayed Alterations of Synaptic Plasticity in Basolateral Amygdala - Zhang, Huan-Huan; Meng, Shi-Qiu; Guo, Xin-Yi; Zhang, Jing-Liang; Zhang, Wen; Chen, Ya-Yun; Lu, Lin; Yang, Jian-Li; Xue, Yan-Xue (Frontiers in Psychology, 2019)
Exposure to acute traumatic stress events is a direct cause of post-traumatic stress disorder (PTSD). Amygdala is suggested to be involved in the development of PTSD. In our previous study, different activation patterns of glutamatergic and GABAergic neurons in early and late stages after stress were found. However, the neural plastic mechanism underlying the role of basolateral amygdala (BLA) in post-traumatic stress disorder remains unclear. Therefore, the main purpose of this study was to investigate time-dependent morphologic and electrophysiological changes in BLA during the development of PTSD. We established the rat model of PTSD using single prolonged stress (SPS) procedure. We found that 1 day after SPS, the rats showed normal anxiety behavior and there were no changes in either dendritic spine density or synaptic transmission in BLA. However, ten days after SPS, rats showed enhanced anxiety behavior in rats and increased density of spines in the BLA. The frequency of miniature excitatory and inhibitory postsynaptic currents in the BLA also increased 10 days after SPS exposure. Our results suggested that after traumatic stress, BLA displayed delayed increase in both spinogenesis and synaptic transmission, which may contribute to the development of PTSD.